(untitled) (Research, Society and Development, 2022)
Teenage pregnancy is considered a public health problem with significant changes in the body and in life. This study aimed to investigate the bodily and contextual changes in adolescent mothers in a private referral service in the city of Fortaleza-CE. Pregnant adolescents were interviewed regarding bodily and contextual changes, from August to October 2021, the data were tabulated by the SSPS version 20.0 to perform the descriptive analysis, considering the Confidence Interval (CI) of 95%. Results from the sample of 10 pregnant adolescents, mean age of 17.2 years; showed that the economic impact is closely linked to the educational impact, the first menarche the average is 11.2 years; which contributed to these young women starting an active sexual life at a very young age, with respect to the first sexual intercourse the average is 14.4 years; the number of partners the average is 4.6. The lack of knowledge and information about contraceptive methods and care to be taken in sexual life prevailed in this study. The body changes faced by these adolescents were evidenced, such as increased breasts and belly (90%), swelling in the joints, which caused pain and numbness in the body (50%). It is concluded that addressing the topic and the means of preventing pregnancy at school and at home, still remains a challenge faced by teachers and parents and competes as a risk factor, and consequently worsening the complications of this clientele makes it urgent to emphasize more directive proposals. with more comprehensive and resolute public policies.